Discurso sobre las mujeres, a las mujeres y de mujeres en el semanario anarquista El Corsario. A Coruña, 1890-1896 - Gérard Brey (Cahiers de Civilisation Espagnole Contemporaine)
El Corsario, a weekly journal published in A Coruña from May 1890, is one of the few spokespaper of the Spanish anarchist movement during the last decade of the 19th century. About fifty articles, written by women or not, deal with the place of women in the family and in marriage, with prostitution or with the exploitation of female labour and the necessity of women to set up organized groups (come together as an organized group) to stop it. Women are also urged to protest against the dispatching of troops to fight the war in Cuba. Some contributions clearly voice feminist points of view, whereas others, sent by anarchistic activists women, talk about non specifically subjects feminine, such as repression.